The Efficacy of a Proposed Program Based on Employing Visual Thinking in the Achievement of Teaching Thinking Subject for Students of Faculties of Education - et. al., Hussam Salam Jaber, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Adopting a proposed program based on employing visual thinking for teaching thinking for students of the fourth stage in the departments of educational and psychological sciences in the college of education and identifying its effectiveness are the key objective of the current research. The researcher chose a sample consisting of (41) male and female students from the department of Educational and Psychological Sciences at the College of Education Ibn Rushd / University of Baghdad. After preparing the required tools and applying the experiment, he reached to a result that the students of the experimental group are superior over the students of the control group in the post-achievement test. This gives an indication that the proposed program is effective. The researcher recommended a number of recommendations and suggestions.